Conformational Dynamics of Mitochondrial Inorganic Pyrophosphatase hPPA2 and Its Changes Caused by Pathogenic Mutations - Ekaterina Bezpalaya; Svetlana Kurilova; Nataliya Vorobyeva; Elena Rodina (Life)
Inorganic pyrophosphatases, or PPases, are ubiquitous enzymes whose activity is necessary for a large number of biosynthetic reactions. The catalytic function of PPases is dependent on certain conformational changes that have been previously characterized based on the comparison of the crystal structures of various complexes. The current work describes the conformational dynamics of a structural model of human mitochondrial pyrophosphatase hPPA2 using molecular dynamics simulation, all-atom principal component analysis, and coarse-grained normal mode analysis. In addition to the wild-type enzyme, four mutant variants of hPPA2 were characterized that correspond to the natural pathogenic variants causing severe mitochondrial dysfunction and cardio pathologies. As a result, we identified the global type of flexible motion that seems to be shared by other dimeric PPases. This motion is discussed in terms of the allosteric behavior of the protein. Analysis of the observed conformational dynamics revealed the formation of a binding site for anionic ligands in the active site that could be relevant to enzyme catalysis. Based on the comparison of the wild-type and mutant PPases dynamics, we suggest the possible molecular mechanisms of the functional incompetence of hPPA2 caused by mutations. The results of this work allow for deeper insight into the structural basis of PPase function and the possible effects of pathogenic mutations on the protein structure and function.